Sedimentology, Stratigraphy and Micropaleontology of Pre- and Early-Champlain Sea Fine-Grained Facies from the Foster Sand Pit, Ottawa, Ontario - Naldrett, Dana (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1988)
ABSTRACTThe Foster sand pit exposes pre- to late-Champlain Sea sediments containing 4 litho/biofacies. These are, from oldest to youngest: Faciès 1- cross-stratified sand and diamicton deposited as late-glacial, ice-proximal subaqueous outwash. Faciès 2- laminated silt and clay rhythmites with a sparse Candona cf. C. subtriangulata ostracode fauna deposited in a deep, proglacial lake preceding the Champlain Sea, Fades 3- massive to rarely laminated silty clay with dominant foraminifera Elphidium bartletti, Protelphidium orbiculare and Cassidulina crassa represents the first glaciomarine deposition in Champlain Sea water 30-100 m deep with a paleosalinity of 22-33 %o. Faciès 4- mixed bedding of sand and mud, with a microfossil assemblage dominated by the Elphidium/Protelphidium complex representing an intertidal offlap sequence. Water depths during deposition of Faciès 4 dropped to 10-30 m. and paleosalinity dropped to 18-28 %o.. This study recognizes a pre-Champlain Sea proglacial lake, assigns subaqueous outwash deposits to an earlier time than previously believed and documents changes in bottom water characteristics of the early Champlain Sea based on sedimentary and microfossil evidence.